Natural orifice translumenal endoscopic surgery - Kalloo, Anthony, 1955-; Marescaux, J. (Jacques); Zorron, Ricardo (Hoboken : John Wiley & Sons, 2012)
Natural Orifice Translumenal Endoscopic Surgery (NOTES) has the potential to change the practice of surgery as we know it. Proponents say advantages over laprascopic surgery include lower anesthesia requirements, faster recovery and shorter hospital stays, avoidance of transabdominal wound infections, less immunosuppression, better postoperative pulmonary and diaphragmatic function, and the potential for "scarless" abdominal surgery. In this text/video set, the leading world expert in NOTES shares his experience. Three sections cover fundamentals, current clinical applications and techniques.
25: Training the Gastroenterologist for NOTES; 26: Training the Surgeon for NOTES; 27: Simulator-based Training of NOTES Procedures; 28: NOTES: Possibilities for the Future; Index.
Print version record.
Keywords: Gastrointestinal system -- Endoscopic surgery; Natural Orifice Endoscopic Surgery -- education; Natural Orifice Endoscopic Surgery -- methods; Medicine; MEDICAL -- Lasers in Medicine; Gastrointestinal system -- Endoscopic surgery; Electronic books